No abrupt change in redox condition caused the end-Permian marine ecosystem collapse in the East Greenland Basin - Nielsen, Jesper K.; Shen, Yanan (沈延安); Piasecki, Stefan; Stemmerik, Lars (Earth and Planetary Science Letters, 2010)
Multiple observations have revealed that environmental disturbances may have been linked to the end-Permian extinction and delayed biotic recovery. Biogeochemical constraints on the temporal and spatial changes of mass oceanic redox chemistry during the Permian-Triassic interval are essential to evaluate global significance of previous hypotheses and to improve our understanding of extinction and recovery processes. To investigate redox ocean chemistry change associated with the end-Permian extinction and subsequent delayed biotic recovery, we examine framboidal pyrites as well as sulfur isotopic compositions of pyrites from the East Greenland Basin. The size distributions of framboidal pyrites in sediments from a continuous section across the Permian-Triassic boundary reveal that sulfidic conditions in water columns were established about 0.7 m above the extinction event in the East Greenland Basin. Our detailed examination of framboidal pyrites challenges a leading hypothesis that euxinia in the photic zone caused the end-Permian ecosystem collapse. We identify several positive and negative S-isotopic shifts before and after the extinction event and demonstrate that a positive S-isotopic shift is not indicative of an abrupt change of redox chemistry in water columns, in contrast to previouos claims. The integration of isotope and framboidal pyrite data provides a nearly continuous record of ocean chemistry evolution and new insights into the end-Permian extinction and delayed biotic recovery in the East Greenland Basin. (c) 2010 Elsevier B.V. All rights reserved.